Ekstraksi ZnO Limbah Baterai Zn-C sebagai Katalis ZnO-Zeolit untuk Degradasi Air Limbah Laundry Berdasarkan Massa dan Waktu Kontak - Yuniar; Wasiran, Yulianto; Yuliandi, Rizki Brillian; Oktaviani, Erika Dwi; Safira, Asri; Novita, Sherly Fitria (Jurnal Serambi Engineering, 2026)
By utilizing waste from Zn-C batteries, it is possible to produce ZnO semiconductor compounds from waste water laundry, which fall under the category of photocatalysts that can decompose harmful organic and inorganic compounds from waste laundry. The research method employed is coprecipitation, which involves synthesizing ZnO through a solution precipitation process, followed by mixing it with zeolite and testing the photocatalyst's activity with varying contact times of 30, 60, 90, and 120 minutes, as well as different weights of ZnO-Zeolite photocatalysts at 0.5, 0.75, and 1 gram. The characterization results of ZnO-Zeolite indicated a crystal size of 23.94 nm and a band gap energy of 2.98 eV. To evaluate the effectiveness of the ZnO-Zeolite photocatalyst, parameters such as pH, Chemical Oxygen Demand (COD), and the degradation of surfactant compounds in laundry waste were analyzed using UV-Vis Spectrophotometry. The findings revealed a decrease in pH from level of 9.18 to 7.25, and a reduction in COD from 269 mg/L to 64 mg/L, representing a percentage decrease of 76.21%. Additionally, the degradation of surfactant levels dropped from 2.817 mg/L to 0.035 mg/L, achieving a degradation percentage of 98.76% with a catalyst mass of 0.75 g and a contact time of 90 minutes.